2017
DOI: 10.1103/physrevphyseducres.13.020102
|View full text |Cite
|
Sign up to set email alerts
|

Energy Project professional development: Promoting positive attitudes about science among K-12 teachers

Abstract: Promoting positive attitudes about science among teachers has important implications for teachers' classroom practice and for their relationship to science as a discipline. In this paper, we report positive shifts in teachers' attitudes about science, as measured by the Colorado Learning Attitudes about Science (CLASS) survey, over the course of their participation in a professional development course that emphasized the flexible use of energy representations to understand real world scenarios. Our work contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The success factor of a PD is highly dependent on a teacher's positive attitude as they help the teachers generate their knowledge and skills (Robertson & Daane, 2017). However, the success of the PD programme is always linked to a teacher's positive attitude.…”
Section: Discussionmentioning
confidence: 99%
“…The success factor of a PD is highly dependent on a teacher's positive attitude as they help the teachers generate their knowledge and skills (Robertson & Daane, 2017). However, the success of the PD programme is always linked to a teacher's positive attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that teachers participating in our PD have had significant, large affective learning gains on the Colorado Learning Attitudes about Science Survey (CLASS) (Robertson & Daane, ). Other research about our PD has documented teachers’ learning through the study of productive conversations about energy concepts (such as representations, degradation, dissipation, and conservation) (Alvarado, Daane, Scherr, & Zavala, ; Daane, McKagan, Vokos, & Scherr, ; Daane, Vokos, & Scherr, , , ).…”
Section: General Instructional Contextmentioning
confidence: 99%